The Degree of t-System Remodeling Predicts Negative Force-Frequency Relationship and Prolonged Relaxation Time in Failing Human Myocardium - Abu-Khousa, Maha; Fiegle, Dominik J.; Sommer, Sophie T.; Minabari, Ghazali; Milting, Hendrik; Heim, Christian; Weyand, Michael; Tomasi, Roland; Dendorfer, Andreas; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2020)
The normally positive cardiac force-frequency relationship (FFR) becomes flat or negative in chronic heart failure (HF). Here we explored if remodeling of the cardiomyocyte transverse tubular system (t-system) is associated with alterations in FFR and contractile kinetics in failing human myocardium. Left-ventricular myocardial slices from 13 failing human hearts were mounted into a biomimetic culture setup. Maximum twitch force (F), 90% contraction duration (CD90), time to peak force (TTP) and time to relaxation (TTR) were determined at 37°C and 0.2-2Hz pacing frequency. F1Hz/F0.5Hz and F2Hz/F0.5Hz served as measures of FFR, intracellular cardiomyocyte t-tubule distance (∆TT) as measure of t-system remodeling. Protein levels of SERCA2, NCX1 and PLB were quantified by immunoblotting. F1Hz/F0.5Hz (R2=0.82) and F2Hz/F0.5Hz (R2=0.5) correlated negatively with ∆TT, i.e. samples with severe t-system loss exhibited a negative FFR and reduced myocardial wall tension at high pacing rates. PLB levels also predicted F1Hz/F0.5Hz, but to a lesser degree (R2=0.49), whereas NCX1 was not correlated (R2=0.02). CD90 correlated positively with ∆TT (R2=0.39) and negatively with SERCA2/PLB (R2=0.42), indicating that both the t-system and SERCA activity are important for contraction kinetics. Surprisingly, ∆TT was not associated with TTP (R2=0) but rather with TTR (R2=0.5). This became even more pronounced when interaction with NCX1 expression was added to the model (R2=0.79), suggesting that t-system loss impairs myocardial relaxation especially when NCX1 expression is low. The degree of t-system remodeling predicts FFR inversion and contraction slowing in failing human myocardium. Moreover, together with NCX, the t-system may be important for myocardial relaxation.